2011
DOI: 10.1177/016264341102600404
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Map to Support People Who are Blind in Navigation through Real Spaces

Abstract: Most of the spatial information needed by sighted people to construct cognitive maps of spaces is gathered through the visual channel. Unfortunately, people who are blind lack the ability to collect the required spatial information in advance. The use of virtual reality as a learning and rehabilitation tool for people with disabilities has been on the rise in recent years. This research is based on the hypothesis that the advance supply of appropriate spatial information (perceptual and conceptual) through com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Previous research on using VEs for spatial exploration has depicted individuals’ difficulties and unsuccessful performance of subsequent orientation tasks in RS (Munro, Breaux, Patrey, & Sheldon, 2002). Our previous research (Lahav & Mioduser, 2008; Lahav, Schloerb, Kummar, & Srinivasan, 2011), resembling the current findings, described participants’ ability to manipulate spatial information and proceed confidently and successfully to the target during orientation tasks in RS. This research demonstrates the positive effect of BlindAid in the unfamiliar space.…”
Section: Discussionsupporting
confidence: 80%
“…Previous research on using VEs for spatial exploration has depicted individuals’ difficulties and unsuccessful performance of subsequent orientation tasks in RS (Munro, Breaux, Patrey, & Sheldon, 2002). Our previous research (Lahav & Mioduser, 2008; Lahav, Schloerb, Kummar, & Srinivasan, 2011), resembling the current findings, described participants’ ability to manipulate spatial information and proceed confidently and successfully to the target during orientation tasks in RS. This research demonstrates the positive effect of BlindAid in the unfamiliar space.…”
Section: Discussionsupporting
confidence: 80%
“…Research results show that during the exploration in the VEs, the participants mostly used RS exploration strategies, such as perimeter, grid, or object to object (Lahav and Mioduser, 2004;Lahav et al, 2011). Lahav and Mioduser (2004) found that some of the participants tended to count steps to be able to estimate dimensions and distances between the environment's components.…”
Section: Research Dimensionmentioning
confidence: 98%
“…These results show that most of the participants (60-100 percent) explored the VE successfully. Some of the VE systems used a haptic device, such as a virtual cane (D'Atri et al, 2007;Lahav and Mioduser, 2004;Lahav et al, 2011;Lé cuyer et al, 2003;Pokluda and Sochor, 2003;Tzovaras et al, 2004). These research participants reported that the different virtual canes were useful for active exploration (collision and texture feedback) and as passive guidance (navigation effects).…”
Section: Research Dimensionmentioning
confidence: 99%
See 2 more Smart Citations